2015
DOI: 10.2527/jas.2014-8439
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-protein or conventional canola meal on growth performance, organ weights, bone ash, and blood characteristics of weanling pigs

Abstract: An experiment was conducted to evaluate effects of 2 high-protein canola meals (canola meal A [CMA]: 45.69% CP and canola meal B [CMB]: 46.97% CP) and a conventional canola meal (CM-CV: 35.10% CP) on growth performance, organ weights, bone ash, and blood parameters of weanling pigs. Inclusion rates of canola meal (CM) in the diets were 10, 20, 30, or 40% for CMA and CM-CV, whereas inclusions were 10, 20, or 30% for CMB. A control diet containing no CM was also formulated. Therefore, 12 diets were used in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
26
5

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 35 publications
10
26
5
Order By: Relevance
“…Enlargement of thyroid glands, liver and kidneys has been reported in many animal studies after intake of high glc rapeseed meal, and this effect has especially been associated with high levels of progoitrin (Schone et al, ; Spiegel et al, ). The inclusion of RPC into the feed did increase liver size in piglets compared to the control group, as also found by others (Hulshof et al, ; Parr et al, ; Schone et al, ; Spiegel et al, ). This may be a result of nitrile formation in the rapeseed products, as intake of nitriles is associated with increased weight of kidney and lesions in kidneys and liver (Nishie & Daxenbichler, ).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Enlargement of thyroid glands, liver and kidneys has been reported in many animal studies after intake of high glc rapeseed meal, and this effect has especially been associated with high levels of progoitrin (Schone et al, ; Spiegel et al, ). The inclusion of RPC into the feed did increase liver size in piglets compared to the control group, as also found by others (Hulshof et al, ; Parr et al, ; Schone et al, ; Spiegel et al, ). This may be a result of nitrile formation in the rapeseed products, as intake of nitriles is associated with increased weight of kidney and lesions in kidneys and liver (Nishie & Daxenbichler, ).…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, there was no effect on ADFI, ADG and F:G from feeding with RPC-UXW despite the higher glc content and extra heat treatment. Similar results were demonstrated in other piglet studies with double-low rapeseed products, with RPC (Eggum et al, 1985;Zhou et al, 2016) and with solvent-extracted rapeseed meals (Landero et al, 2012), while a few studies found reduction in ADFI (Danielsen et al 2010;Landero et al, 2011) and also in ADG (Hulshof, van der Poel, Hendriks, & Bikker, 2016;Parr et al, 2015;Wang et al, 2017). Generally, the accepted level of rapeseed glc varies between studies, which may be linked to the fact that most studies measure the level in the cake, and lack information about the potential amount of the different glc transformation products.…”
Section: Animal Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…Thus, the poor digestibility or allergenicity of rapeseed protein is considered as a negative factor in the nutritional value of rapeseed co-products either in animal feeds or human diets (Wanasundara, 2011). However, in contrast to many investigations reporting a low digestibility value of CP and amino acids in RSM (Adedokun et al, 2008;Zhou et al, 2013;Kozlowski and Jeroch, 2014;Le et al, 2014;Li et al, 2015), a recent growth performance trial testing RSM resulted in a very similar rates of body weight gain to the control non-rapeseed diet when evaluated in non-ruminants (Parr et al, 2015). This suggests that protein rich co-products might have a good nutritional quality.…”
Section: Discussionmentioning
confidence: 99%
“…conventional canola meal (CM-CV; Liu et al, 2014;Berrocoso et al, 2015;Parr et al, 2015). Canola meal also provides significant quantities of P and Ca to diets Rodríguez et al, 2013), but some Ca and more than 60% of total P in canola meal is bound to phytate (NRC, 2012).…”
mentioning
confidence: 99%